Dominance of Anopheles Maculatus over Etawa Crossbred Goats Population in Malaria Pre-Elimination Areas - Didik Sumanto; Sayono Sayono; Tri Dewi Kristini; Wahyu Handoyo; Yagoob Garedaghi (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2022)
Malaria disease is transmitted by the Anopheles sp vectors. The climate and environmental changes will in fact affect the life and bionomic vector of Anopheles sp. The Anopheles species in an area are strongly influenced by the availability of brood stocks. Such efforts to control malaria have to be in line with controlling the Anopheles population in that area. Information on the behaviors, bionomic characteristics, and habitat preferences of Anopheles species is thus needed. It is very important to select a control program according to the types of vectors to be controlled. This study aimed to examine the dominance of Anopheles species in malaria-endemic areas with currently pre-elimination status with the Etawa goats population. A field survey was necessarily conducted to catch mosquitoes during nighttime. Catching using human bait and livestock bait started from 06.00 pm to 04.00 am. Identification of species morphology used the WRBU guidelines. The catch results were dominated by Anopheles (63.64%), followed by Culex (27.27%) and Aedes (9.09%), respectively. The caught Anopheles consisted of An. maculatus (64.29%), An. subpictus (28.57%) and An. aconitus (7,14%) respectively. It was found that An. Maculatus type surprisingly still dominated the mosquito population in the malaria pre-elimination area in Purworejo. Thereby, it is important to develop such a malaria control method based on mosquito attack diversion because the dominant vector in this area is more zoophilic.